Absence of AKT1 mutations in glioblastoma. - Fonnet E Bleeker (Public Library of Science (PLoS), 2009)
Background Oncogenic activation of the PI3K signalling pathway plays a pivotal role in the development of glioblastoma multiforme (GBM). A central node in PI3K downstream signalling is controlled by the serine-threonine kinase AKT1. A somatic mutation affecting residue E17 of the AKT1 gene has recently been identified in breast and colon cancer. The E17K change results in constitutive AKT1 activation, induces leukaemia in mice, and accordingly, may be therapeutically exploited to target the PI3K pathway. Assessing whether AKT1 is activated by somatic mutations in GBM is relevant to establish its role in this aggressive disease. Methodology/principal findings We performed a systematic mutational analysis of the complete coding sequence of the AKT1 gene in a panel of 109 tumor GBM samples and nine high grade astrocytoma cell lines. However, no somatic mutations were detected in the coding region of AKT1. Conclusions/significance Our data indicate that in GBM oncogenic deregulation of the PI3K pathway does not involve somatic mutations in the coding region of AKT1.